Surface Patterning of Closed Nanochannel Using VUV Light and Surface Evaluation by Streaming Current - Kyojiro Morikawa (MDPI AG, 2021)
In nanofluidics, surface control is a critical technology because nanospaces are surface-governed spaces as a consequence of their extremely high surface-to-volume ratio. Various surface patterning methods have been developed, including patterning on an open substrate and patterning using a liquid modifier in microchannels. However, the surface patterning of a closed nanochannel is difficult. In addition, the surface evaluation of closed nanochannels is difficult because of a lack of appropriate experimental tools. In this study, we verified the surface patterning of a closed nanochannel by vacuum ultraviolet (VUV) light and evaluated the surface using streaming-current measurements. First, the C18 modification of closed nanochannels was confirmed by Laplace pressure measurements. In addition, no streaming-current signal was detected for the C18-modified surface, confirming the successful modification of the nanochannel surface with C18 groups. The C18 groups were subsequently decomposed by VUV light, and the nanochannel surface became hydrophilic because of the presence of silanol groups. In streaming-current measurements, the current signals increased in amplitude with increasing VUV light irradiation time, indicating the decomposition of the C18 groups on the closed nanochannel surfaces. Finally, hydrophilic/hydrophobic patterning by VUV light was performed in a nanochannel. Capillary filling experiments confirmed the presence of a hydrophilic/hydrophobic interface. Therefore, VUV patterning in a closed nanochannel was demonstrated, and the surface of a closed nanochannel was successfully evaluated using streaming-current measurements.